Analysis of Competitiveness Factors of Wind Power: A Case study in the Alto Sertão Wind Complex in the State of Bahia, Brazil - Marques, Rogério; Fernandes, Fábio Matos; Silva, Marcelo Santana; Martins, Luís Oscar; Mendonça Freires, Francisco Gaudêncio (International Journal of Energy Economics and Policy, 2023)
The increasing demand for electricity in Brazil has significant economic implications for the energy market. In this context, it is important to investigate alternative sources that can meet this demand, as well as understand the key factors that influence this process. The Wind power is considered one of the most promising sources, due to its exponential growth, cost-effectiveness, and continuous supply assurance. However, given the consolidation of fossil fuel sources in economic and technical terms, it is necessary to understand the factors of competitiveness that can be considered as potentials or constraints for the full development of wind energy. Thus, the overall objective of this research was to analyze the competitiveness factors of wind energy, using the Alto Sertão wind complex located in the state of Bahia as a case study. The methodology used in this research was based on an exploratory documentary approach, which sought regulated information from government agencies. The research predominantly used secondary data sources, combined with conducting interviews. The results indicate three factors that confer competitiveness to the sector. Unlike other states in the Northeast, which have a higher occurrence of winds along the coast, Bahia has its greatest wind potential concentrated in the interior, east of the São Francisco River, from the Espinhaço Range to municipality of Juazeiro - BA. This is due to low cloudiness and the process of high atmospheric pressure moving towards the Northeast, resulting in excellent quality winds for wind energy generation, which makes the region competitive.